ANALISIS EKSISTENSI LAYANAN GO-FOOD DALAM MENINGKATKAN PENJUALAN PADA RUMAH MAKAN DI BANJARMASIN - Muhammad Hasan; Dwi Wahyu Artiningsih; Teguh Wicaksono (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2019)
This study aims to examine: (1) Knowing the extent to which the existence of online transportation (Go-food) in increasing sales of restaurants in Banjarmasin. (2) Knowing the economic and social impacts of restaurant business people in Banjarmasin after cooperating with Go-food. This study used a descriptive qualitative research design with observation, interviews and documentation. The sample in this study was a restaurant in Banjarmasin that had collaborated with Go-food with a focus on five restaurants in Banjarmasin. The results showed (1) that the existence of online transportation (Gofood) in increasing sales of restaurants in Banjarmasin, this identified the existence of online transportation (Go-food) to five restaurants experienced a significant increase in sales, which affected the increase in income. (2) after cooperating with Go-food, restaurant businesses in Banjarmasin have a positive impact on social and economic influences such as the addition of employees and an increase in annual income